PENGELOLAAN PERPUSTAKAAN SEKOLAH SMAN 1 BUKIT SUNDI DAN SMAN 1 LEMBANG JAYA KABUPATEN SOLOK - Desriyeni Desriyeni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
IbM program aims to provide understanding to partners about the concept and implementation of library management in accordance with library management procedures. The targets to be achieved are as follows. 1) Improving the quality of library staff in managing the library through the manterhadap the nature of the library. A minimum of 75 training materials can be mastered by the trainees. 2) Produce school library management guidelines to facilitate library staff in managing the library. 3) Applying knowledge in school library management. Output target in the form of process is the occurrence of improvement of target audience ability in understanding understanding, concept and process of management and utilization of school library. Output target in the form of product is at least 75% of participants produce library materials that have been processed and at least 75% of participants generate library catalogs to facilitate the process of retrieval. The methods offered to solve the problem of library management are: through the creation of a library management module that contains the concepts of library management; socialization and training of school library management. Implementation of the activity begins with the preparation of training materials, copying, presenting the material, and training with individual guidance. To evaluate the achievement of objectives begins by measuring the candidate's initial capability, followed by an evaluation to measure participants' ability at each stage of the activity, and a final evaluation to measure achievement purpose of program activities. Training activities carried out smoothly in accordance with the expected objectives of this program activities. This activity received a positive response from various parties and trainees in the management of school libraries. So it is expected to provide better service and the existence of school library will be more real in the community.